Measurements of acoustic impedance in Indians - Basavaraj V (Journal of All India Institute of Speech and Hearing, 1970)
Impedance measures-tympanometry, acoustic impedance, and acoustic reflex threshold were determined on 136 Indian subjects (191 ears) using electro-acoustic bridge (Madsen ZO 70).  The subjects included normal and pathological, varying in age from 6-56 years. Sex and age differences were observed with regard to static compliance and acoustic impedance. Any conclusion rerarding the norms for acoustic impedance cannot be drawn as there is overlapping of pathogical and normal ears with regard to acoustic impedance. The normals obtained a wider range of 682-5840 acoustic ohms. Varying of air pressure in the ear canal had significant effect on acoustic reflex .threshold.